AuCu@Pt Nanoalloys for Catalytic Application in Reduction of 4-Nitrophenol - Sadia Mehmood; Naveed Kausar Janjua; Farhat Saira; Hicham Fenniri (Journal of Spectroscopy)
To enhance and optimize nanocatalyst ability for nitrophenol (4-NP) reduction reaction we look beyond Au-metal nanoparticles and describe a new class of Au nanoalloys with controlled composition for core of AuCu-metals and Pt-metal shell. The reduction of 4-NP was investigated in aqueous media spectroscopically on 7.8 nm Au nanospheres (AuNSs), 8.3 nm AuCuNSs, and 9.1 nm AuCu@Pt core-shell NSs in diameter. The rate constants of the catalyzed reaction at room temperature, activation energies, and entropies of activation of reactions catalyzed by the AuCu@Pt core-shell NSs are found to have different values to those of the pure metal NSs. The results strongly support the proposal that catalysis by nanoparticles is taking place efficiently on the surface of NSs. These core-shell nanocatalysts exhibited stability throughout the reduction reaction and proved that heterogonous type mechanisms are most likely to be dominant in nanoalloy based catalysis if the surface of the NSs is not defected upon shell incorporation.